MEDICAL STUDENTS’ RESEARCH MENTORING PROGRAM AT CENTRAL PARK MEDICAL COLLEGE, LAHORE, PAKISTAN - Hidayat, Mariyah; Babar, Shazia (Journal of Ayub Medical College Abbottabad, 2021)
Background: Postgraduation programs, including clinical specialties, have inculcated a mandatory research component, yet no initiatives are taken for the promotion of research at the undergraduate MBBS programs across Pakistan. This study has highlighted a research mentoring program at undergraduate level conducted at Central Park Medical College (CPMC), Lahore, which developed research interest from the start of MBBS. The objective of the study was to explore the perception of mentees and mentors regarding the research mentoring program at CPMC. Method: This observational cross-sectional study, conducted from April-December 2019, included 500 MBBS students, along with their 50 research mentors. After institutional ethical approval and written informed consent, a survey questionnaire was circulated in November, amongst mentors and mentees, to explore their perspective regarding research program. The data was entered in SPSS version 21. Frequency and Reliability analysis by Cronbachs Alpha was done Results: The reliability of the questionnaire was 0.82. Around 80-90 percent of the mentors believed that it developed intellectual skills of both mentors and mentees, but the students had a mixed response. After 7 months, there was one article published, four were accepted for publication, ten were under peer review in HEC recognized journals, and majority was observational cross-sectional studies/case reports. Conclusion: It proved to be a mutually beneficial program and facilitated research activities of both mentors and mentees. It is suggested to introduce structured research mentoring program into the undergraduate curriculum of other medical institutions too.